The crisis of democratic governance in Southeast Asia - Croissant, Aurel; Bünte, Marco (Palgrave Macmillan, 2011)
"Democracy in Southeast Asia is in crisis. The contributors to this volume argue that this is a crisis of democratic governance. They look into its causes, consequences, and prospects, comparing themes of democratic governance in Southeast Asia, such as political culture, civil society, political parties, and institutions and human rights"--
Includes index
Keywords: Southeast Asia -- Politics and government -- 1945-; Südostasien; Aufsatzsammlung; Konferenzschrift; Demokratisierung; Demokratie